Specific Barriers for Quadruple Helix Innovation Model Development – Case of Croatia - Jan Klasinc (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
There has been a lot of theoretical discussion about triple helix and quadruple helix methodologies for innovation and knowledge transfer in the context of local development and even smart cities. The goal of this paper is to describe specific barriers related to ICT uptake, usage and development related to knowledge based capital and their role in Croatia, especially in the context of passing from triple helix (academia, business, government) to quadruple helix (academia, business, government, NGOs/citizens) model. Specific barriers exist in each country, and they may be divided into technological, organisational, human, societal and/or cultural barriers. The case of Croatia is specifically analysed and compared to other countries in the region and in the EU. The lack of participative culture and other criteria influencing social dynamics are particularly addressed in order to reach a conclusion about country specific barriers and provide policy advice for decision makers.
Keywords: O35; O31; 330; innovation; social entrepreneurship; quadruple helix; knowledge based capital; country specific barriers